PENDAMPINGAN ASSESSMENT FOR LEARNING (AFL) GURU BAHASA INGGRIS SMPN 9 RUTENG, FLORES - Hieronimus Canggung Darong; Stanislaus Guna; Yosefina Helenora Jem; Erna mena Niman (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
Teaching is an integrated activity with learning goals or objectives and assessment process. As such, it is conducted on the basis of particular learning goals which subsequently requires assessment activities to look into the impact of teaching on students learning process. The aim of this community service is to furnish the knowledge regarding the assessment process, particularly Assessment for Learning (AfL) of English teachers involving in MGMPS of English Subject at SMPN 9 Ruteng. The method used was in- service training employing Information Processing Theory namely information encoding, information decoding, infromation storing, and information rehearsal. The results have indicated that the English teachers involving in MGMPS SMPN 9 Ruteng were able to make a good instructional design along with the Assessmenf for Learning (AfL). It was proven on their works as they did the task provided by the community service team. Yet, they need to have a further professional development on curriculum and asessment following the changes and goverment policies on education.